Actinomycosis: Case report of an unusual cause of diaphragmatic herniation. (August 2021) - Hurwich, Andrew; Pennell, Christopher; Prasad, Rajeev
Abstract: Introduction: We present a case of actinomycosis which resulted in a symptomatic diaphragmatic hernia requiring operative repair, an unusual complication not found in the literature. Actinomycosis is a chronic, slowly progressive infection caused by the bacterial genus Actinomyces which characteristically causes necrosis and abscess formation in a myriad of organ systems. Case presentation: A 5 year old male presented with nonspecific symptoms which were, after a short delay, identified as actinomycosis and treated with appropriate antibiosis. His infection was complicated by development of a diaphragmatic hernia, which subsequently became symptomatic and required surgical repair. Clinical discussion: While this diaphragmatic hernia is an unusual complication of actinomycosis not previously found in the literature, the patient's delayed diagnosis of the infection is typical. Surgical intervention was warranted for symptoms of the sequelae of the disease, not control of the disease itself. Conclusion: Laparoscopic repair of the multiple diaphragmatic defects was successful with a intraperitoneal on-lay biologic mesh, with resolution of symptoms. It is possible the need for surgical intervention in future cases of actinomycosis could be avoided with higher index of suspicion leading to earlier diagnosis. Highlights: Actinomycosis is an indolent, difficult to diagnose infection. Actinomycosis causes a wide variety of pathology. Intraperitoneal onlay mesh for repair of diaphragmatic hernia.